(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background : There is increasing evidence that localized irradiation of the tumor may also modify the tumor microenvironment and generate inflammatory cytokines. Objective: This study is aimed to clarify the effect of proton beam radiation on the interferon (IFN-?, IFN-?, IFN-?) and nucleotide. Methods: The Microsoft "The Stopping and Range of Ions in Matter (TRIM-SRIM)" version 1998, and 2003 was used. A model of targeting certain interferon (IFN-?, IFN-?, IFN-?) as well as the nucleotide pair was created. Each target was subjected to proton radiation of hydrogen [H], helium [He], or carbon [C] at different range of energy seeking for the Bragg’s peak. Result: The results showed that the cross sections IFN-?, IFN-?, IFN-? and nucleotide targeted by proton therapy were 0.9776, 0.8317, 0.8297 and 0.7305 [keV/(µg/cm2)] for hydrogen ion, and 2.3354, 2.3414, 2.3377, 2.0842[keV/(µg/cm2)] for helium ion, and 8.3032, 8.3198, 8.3109, 7.5394 [keV/(µg/cm2)] for carbon ion respectively. Conclusions: It concludes that targeting of well precise located tumor with proton beam radiation therapy resulted in nucleotide damage of cancer cell without affecting the immune system in term of interferon surveillance. Key words: Proton, Nucleotide, Interferon